BAGAIMANA ADAPTASI SISTEM KERINGANAN PEMBAYARAN PT JASA RAHARJA MADIUN SAAT COVID-19? - Selvia Angger Sari; Supri Wahyudi Utomo; Elana Era Yusdita (RISTANSI: Riset Akuntansi, 2022)
This study aims to determine the application system for IWKBU payment relief and the implementation of the tax relief system during the pandemic for taxpayers for 3 months to ease the payment of SWDKLLJ at PT Jasa Raharja (Persero) Madiun Branch Representative Office during the Covid-19 period. The type of research used is descriptive qualitative, researchers conducted interviews with informants, namely employees of PT Jasa Raharja (Persero) Madiun Branch. The results of this research are Jasa Raharja Madiun employees that income during this pandemic is very low, as well as a system of asking for waivers for PO Buses and a 3 month tax relief system is applied for taxpayers because with the pandemic the community's economy is declining and the PO Bus cannot operate. Then the JR-Ku application can make payments easier and can be more effective and efficient in time.